Predictors of Internet Addiction in Middle Adolescence: Social, Emotional Loneliness and Digital Gaming - Serhat Turan; Selda Uzun; UÄŸur Alemdar (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2023)
The research aims to determine how much Internet addiction, an important problem in middle adolescence, is explained by social and emotional loneliness and digital game-playing duration. For this purpose, 283 (108 females+175 males) middle-adolescent individuals participated in the study. â€œPersonal Information Form,â€ â€œSocial and Emotional Loneliness Scale (SELSA),â€ and â€œInternet Addiction Scale (IAS)â€ were used as data collection tools in the research. The data collected online were coded and transferred to the SPSS program, and descriptive statistics, Pearson correlation, and Regression techniques were used in statistical analysis. In the study, the level of significance was taken as p<.05. According to the results of the analysis, there is a low, significant, and positive correlation between SELSA and IAS and a low, significant, and positive correlation between SELSA and digital game playing duration and a low, significant, and positive correlation was found between IAS and the duration of playing digital games. It was determined that the statistical analysis results did not show a significant difference in the gender variable of the IAS and SELSA scores. As a result of the regression analysis, it was seen that SELSA and digital game-playing duration significantly predicted addiction. SELSA and digital game-playing duration explain 9.6% of the total variance regarding Internet addiction. As a result, it can be said that individuals in middle adolescence experience social and emotional loneliness at a moderate level and are connected to the Internet at a low level.